Obstructive respiratory events transiently impair electromechanical coupling and increase premature ventricular contraction rate in a drug-induced Long-QT-2 pig model. (25th November 2020) - Linz, B; Flethoj Madsen, M; Hotbjerg Hansen, M; Melis Hesselkilde, E; Saljic, A; Hohl, M; Wirth, K; Linz, D; Sattler, M; Tfelt-Hansen, J; Jespersen, T
Abstract: Background: Obstructive sleep apnea (OSA) is characterized by intermittent negative thoracic pressure fluctuations and intermittent hypoxemic events. Recent findings associate OSA with impaired ventricular repolarization during sleep and increased risk of sudden cardiac death, which may have special implications for Long-QT-2-syndrome patients. Therefore, we elucidated changes in ventricular repolarization and electromechanical coupling (electromechanical window; EMW) during either obstructive respiratory events simulated by intermittent negative upper airway pressure (INAP) or hypoxemic events simulated by intermittent hypoxia (IH) in vehicle (VEH) and dofetilide (DOF) treated pigs, as a simulation of drug induced Long-QT-2 syndrome. Methods: In sedated spontaneously breathing pigs, either VEH or DOF (50 μg/kg) was perfused and INAP was applied by a negative pressure device connected to the intubation tube. For IH-application the device was connected and left turned off. INAP or IH was maintained for 75 seconds followed by a ten-minute resting period. In order to evaluate the electromechanical window, the time difference between electrical (QT-duration) and mechanical systole (Q-wave to the end of left ventricular pressure signal, QLVPend) was measured before (pre-INAP/-IH), during and 60 seconds after INAP/IH (post-INAP/-IH). Incidence rates of premature ventricular contractions (PVC) and ventricular tachycardia were compared pre- to post-INAP/-IH. Results: In VEH-pigs, EMW shortened throughout INAP and post-INAP periods steadily (VEH: pre-INAP: 81.69±2.31ms; INAP: 55.65±6.13ms; post-INAP: 38±8.89ms. p=0.008). EMW shortening during post-INAP was associated with an increase in PVCs (VEH: pre-INAP 5.41±1.87 vs. post-INAP 26.5±8.15; p=0.04). In DOF-pigs, INAP-associated EMW-shortening was further potentiated (DOF: pre-INAP: 61.16±7.18ms; INAP: 38.09±9.84ms; post-INAP: 14.93±9.24ms. p=0.016), which was associated with an increase in PVCs (DOF: pre-INAP 4.75±2.36 vs. post-INAP 36.58±10.92; p=0.017). Administration of Atenolol could prevent post-INAP shortening of the EMW and decrease counts of premature ventricular contractions. While desaturations were comparable in INAP and IH, IH did not result in EMW-shortening or increased arrhythmia risk. Conclusion: Transient dissociation of the ventricular electromechanical coupling during a simulated obstructive apnea, but not during IH, creates a dynamic and sympathetically driven arrhythmogenic substrate. Apnea associated ventricular electromechanical uncoupling was aggravated in a drug-induced Long-QT-2 simulation. Whether OSA represents a modifiable arrhythmogenic risk factor in Long-QT-2-patients warrants further studies. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Novo nordisk fonden